THE "GAP MODEL" AS AN ANALITICAL TOOL TO STUDY MIGRATION POLICY IN THE END OF XX CENTURY - Victor Apryshchenko (Гуманитарные и юридические исследования)
The article studies two intellectual models describing modern migration process. The "conflict model" is based on the idea about the gap between government policy in migration sphere and the public opinion. In modern countries this gap is caused by different group interests. The article analyzes different factors enhancing this gap between political declarations and the reality. With the reference to facts the author demonstrates heuristic potential of the model and concludes that in may be considered as an important instrument for the study of migration policy. To achieve the most objective and qualitative scientific conclusions, the author draws attention to the development of migration policy in different countries of the XX century. Analyzing the problems of migration policy, the author faced the problem of uncertainty of the algorithm and methods to determine the exact amount of discrepancy between the official promises of the authorities and the real migration situation. Notably, the so-called "gap method" also reveales the reason of the failed migration policy; according to the author, it is the differentiation in the level of income and the possibility of achieving the desired standard of living, which, in turn, leads to illegal border crossing. Studying the problems of implementation of migration policy, the author finds another reason that complicates the work of the government on this issue. "Political failure" of the migration policy causes public discontent on the part of indigenous population, which, in turn, poses a new challenge to the authorities and promotes the revision of the current migration legislation. Nevertheless, the author does not consider the assessment of public opinion as a serious indicator of the failure of immigration policy, as it is not always an effective criterion to assess the actions of national authorities, as these estimates are not objective and can be announced in the times of economic downturn, therefore, the population can associate economic difficulties with the presence of migrants, which may not always be an objective link.